Innovative approaches in training specialists in conditions of digitalization of education - Каzimova, D.A.; Аbdrasheva, B.Zh.; Baimukanova, М.Т.; Роlupan, K.L.; Мusatai, N.A. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The article discusses the main factors of the introduction of digital educational technologies that contribute to the integration of the information infrastructure of the education of the Republic of Kazakhstan into the world educational environment. Highlighted priorities for creating a unified information educational environment and the introduction of an e-learning system. The legal acts on the implementation of the development of digitalization of education have been implemented. The authors show the main tasks of e-learning in educational institutions in Kazakhstan. Particular attention is paid to the introduction of new educational programs of technical and vocational, higher education. The article describes the possibilities of an innovative approach to the formation of the educational environment in the university during the training of specialists in the conditions of digitalization. The training of specialists in the conditions of digitalization of education dictate the direction of the formation of the educational environment. Therefore, the authors pay special attention to a comparative analysis of the goals and content of training in the system of vocational education and training and universities. On a basis of analysis, the authors focus on the application of an innovative approach to the training of a new generation of specialists in the conditions of digitalization of education.
Білім беруді цифрландыру жағдайында мамандарды даярлаудағы инновациялық тəсілдер
Инновационные подходы при подготовке специалистов в условиях цифровизации образования
Keywords: digital educational technologies; e-learning system; digitalization of education; educational programs; systems of technical and vocational education; higher education; educational environment; training